SchedMonSys Development of an effective monitoring system: basis for an schedule management workplace - Dela Rosa, Jerick M.; Desoloc, Ronnel A.; Abar, Lahren Jude D. (b)
The Schedule Monitoring System (SchedMonSys) provides a web-based platform with user-friendly interface for maintenance staff schedules and appointment maintenance staff schedules and appointment maintenance staff schedules. The system{92}s goal is to create an efficient way to report and schedule tasks to the maintenance staff, and report back for task completion without direct contract. Optimize the required time to address a report according to the schedule given for maintaining the utilities. Shows a real-time update on the tasks that have been reported, work in progress, and completed tasks.
Undergraduate thesis.
Keywords: Schedule; Monitoring; Database; Web-based.